Causes of the Northern Gulf of Guinea Cold Event in 2012. Issue 8 (16th August 2021) - Da‐Allada, C. Y.; Agada, J.; Baloïtcha, E.; Hounkonnou, M. N.; Jouanno, J.; Alory, G.
Abstract: Particularly cool sea surface temperatures (SSTs) were observed in 2012 along the Northern Gulf of Guinea coast. This strong cooling event was seen from February to June and reached maxima in the coastal upwelling areas: SST anomalies of −1°C were observed in Sassandra Upwelling area in Côte d'Ivoire (SUC, situated east of Cape Palmas) and SST anomalies of −0.5°C were observed in Takoradi Upwelling area in Ghana (TUG, located east of Cape Three Points). In SUC and TUG regions, the 2012 decrease in SST was the coldest event recorded over the 1990–2018 period (29 years). From the analysis of regional simulations, we show that the mechanisms behind this SST decrease differ in the two regions. In the SUC region, we identify changes in both zonal advection (related to zonal SST gradient changes) and increased vertical mixing as the main drivers of the anomalous cooling. The anomalous vertical mixing is linked to increased vertical shear of the zonal current in response to the Guinea Current strengthening. In the TUG region, acceleration of the southward advection of the surface water, due to the intensification of the meridional Ekman current generated by the strengthening of the zonal wind stress, was identified as the major cause of the SST anomalous cooling. Plain Language Summary: We investigate the causes of the anomalous cooling that happened in the northern Gulf of Guinea coast between February and June 2012 using observations and model data. The abnormal sea surface temperature decrease was pronounced at the upwelling regions of Sassandra in Côte d'Ivoire and Takoradi in Ghana. Results reveal that the anomalous cooling, in the Sassandra upwelling area, was mainly due to changes in both the vertical mixing at the base of mixed layer and zonal advection, whereas only changes in meridional advection explained the anomalous cooling seen in the Takoradi upwelling area. Key Points: Causes of the anomalous cooling seen in the northern Gulf of Guinea coast between February and June 2012 are investigated Sea Surface Temperature anomalies were important in the coastal upwelling regions of Sassandra in Côte d'Ivoire and Takoradi in Ghana Sassandra cooling was due to vertical mixing and zonal advection changes, whereas only meridional advection changes caused Takoradi cooling